Eksplorasi Aspek – aspek Penghambat Penerimaan User Telemedicine pada Daerah Tertinggal di Indonesia - Ari Ardiansyah; Effy Zalfiana Rusfian (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
Utilization of Information and Communication Technology (ICT) has touched various areas of life including the health sector. Telemedicine as a result of the progress of ICT is very much used by midwives (users) as the spearhead of health services, especially for disadvantaged / remote areas. Midwives in remote areas as beneficiaries and use of ICT. So the aim of this study was to identify behavioral factors of Telemedicine users. The research strategy used was a case study in an underdeveloped area of Kupang Regency, East Nusa Tenggara where the mortality rate for pregnant women born was high compared to the mortality rate for pregnant women in other regions in Indonesia. This qualitative research uses in-depth interviews. The results showed that the factors of performance expectancy, effort expectancy, social influence, and facilitating conditions varied greatly. Apart from these factors, it was also found in this study that the diversity of the midwives' level of understanding on telemedicine was highly dependent on the socialization process carried out by the local government.